PENGARUH DAYA TARIK DAN FASILITAS TERHADAP MINAT BERKUNJUNG DI DANAU SITU CIPONDOH - Oktavianus, Rio; Sofiani, Sofiani (Jurnal Ilmiah Global Education, 2023)
Lake Situ Cipondoh is a tourist attraction in the City of Tangerang, which was once a large concave swamp and was built into an artificial lake that can attract the people of Tangerang to travel. This research was conducted to search for the influence of attractions and facilities on visiting interest at Lake Situ Cipondoh. This type of research is quantitative with the method of multiple linear regression analysis with the help of the IBM SPSS 26 program. The data collection technique was carried out by distributing questionnaires to tourists who had visited Lake Situ Cipondoh with a total of 98 people. The results of the data that have been obtained are then analyzed using the SPSS application. The results of the study show the validity and reliability tests, it is known that each dimension and statement has valid and reliable results. In the T and F Tests it is known that the attractiveness and facilities variables have a significant good influence on visiting intentions. From the test results of the coefficient of determination obtained from the attractiveness and facilities variables, there is an influence of 74.7% on the variable of interest in visiting and on the results of the multicollinearity, heteroscedasticity and normality tests it can be seen that there are no symptoms of the test so that they can be normally distributed. The author's suggestion for the Lake Situ Cipondoh area is to be able to improve the existing facilities in the area so that it can encourage more attractiveness for visitors to come back.